Priority Directions for Increasing Emergency Monitoring and Forecasting Effectiveness - Xolikovich, Razzokov Xabib (European Journal of Life Safety and Stability (2660-9630), 2023)
The examination of the data on emergency circumstances reveals that the primary contributors to the risk of emergency situations are fires and other natural catastrophes associated with hazardous natural phenomena, accidents involving moving bodies of water, human-caused accidents, and terrorist attacks. Lib is a serious threat to the nation's economy, residents' safety, and the republic's ability to maintain a steady course of growth. In this regard, the prevention and elimination of emergency situations, the Ministry of Emergency Situations of the Republic of Uzbekistan, the ministries, departments and other organizations that are part of the state system of their prevention and action in emergency situations, monitoring, information exchange and forecasting of natural, man-made and ecological emergency situations single system (hereinafter referred to as the Single System) determines that it is one of the priority and urgent tasks to improve the system of risk management in emergency situations based on increasing the efficiency of monitoring of dangerous natural events and man-made processes and forecasting emergency situations.